Pemberdayaan Ekonomi Masyarakat melalui Optimalisasi Potensi Sumber Daya Alam di Desa Gunungsari Kabupaten Serang - Budi Hasanah; Fuqoha Fuqoha; Rahmi Mulyasih; Ahmad Sururi (Madani : Indonesian Journal of Civil Society, 2021)
The potential of abundant natural resources in Gunungsari Village, Serang Regency, is still unable to improve the economic standard of life of the community, this is due to the lack of community skills and the lack of public knowledge in optimizing the potential of these natural resources into economic added value. This method of community economic empowerment through optimization of natural resource potential in Gunungsari Village, Serang Regency uses an environmental communication strategy which includes 1) Material Stage; 2) Energy Phase; 3) Information Stage, and 4) Evaluation Stage. The results of community service concluded that community economic empowerment through optimizing the potential of natural resources received a positive response and enthusiasm from the community, with the success rate of training program indicators being on an interval scale with an average value of 70% or a fairly good category. Thus it can be concluded that encouraging the skills training of the Gunungsari Village community in utilizing the natural resource potential of the papaya fruit is very important to improve the welfare of rural communities.